Comparison of various methods of temperature measurement in children admitted in the pediatric ward of a tertiary care center - Varadarajan, Poovazhagi; Muthaiyan, Jayakumar; Jayachandran, Ganesh; Sankaran, Anupama; Sankaran, Suresh Kumar (International Journal of Contemporary Pediatrics, 2017)
Background: Temperature measurement is an important procedure in the diagnosis and management of childhood illness. Rectal measurement of temperature is often done with resentment from the child, the parents as well as the physician. Intra aural (Tympanic), temporal artery and axillary measurements are commonly undertaken for temperature recording in children. The aim of the study was to compare the various methods of temperature measurement (intra aural, temporal artery and axillary measurements) in children. This was a hospital based descriptive study (pilot study) from a pediatric tertiary care center. Methods: This was a hospital based descriptive study (pilot study) from a pediatric tertiary care center. 250 children admitted with history of fever in the pediatric ward. All consecutive children with fever were recruited for the study. Children with ear pain, ear discharge and wax in the ear were excluded. Results: Inter-group comparison was performed using student paired t-test. There was no difference in the temperature measured by axillary and temporal artery touch when compared with intra aural. Temperature measured by infra-red temporal at 3 cm showed significant lower temperature. Temporal artery and axillary measurements had a correlation coefficient of 0.74 and 0.64 respectively when compared with intra aural measurement. Conclusions: Temporal artery and axillary measurements are not significantly different from intra aural measurement in children. For the ease of measurement, better correlation, better compliance of the child, temporal artery method can be a reliable preferred temperature measurement in children with fever.